2017
DOI: 10.1186/s12885-016-3011-9
|View full text |Cite
|
Sign up to set email alerts
|

Narrow band imaging versus lugol chromoendoscopy to diagnose squamous cell carcinoma of the esophagus: a systematic review and meta-analysis

Abstract: BackgroundIn the early stage esophageal cancer, changes in the mucosa are subtle and pass unnoticed in endoscopic examinations using white light. To increase sensitivity, chromoscopy with Lugol’s solution has been used. Technological advancements have led to the emergence of virtual methods of endoscopic chromoscopy, including narrow band imaging (NBI). NBI enhances the relief of the mucosa and the underlying vascular pattern, providing greater convenience without the risks inherent to the use of vital dye. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
127
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(131 citation statements)
references
References 27 publications
2
127
0
Order By: Relevance
“…Regarding the comparison between NBI and Lugol chromoendoscopy, three studies found that NBI and ME-NBI have an increased accuracy and specificity when compared with Lugol, although the sensitivity is similar between the two techniques [15-17]. These findings were also confirmed in two recent meta-analyses [18]. …”
Section: Esophagussupporting
confidence: 75%
“…Regarding the comparison between NBI and Lugol chromoendoscopy, three studies found that NBI and ME-NBI have an increased accuracy and specificity when compared with Lugol, although the sensitivity is similar between the two techniques [15-17]. These findings were also confirmed in two recent meta-analyses [18]. …”
Section: Esophagussupporting
confidence: 75%
“…Multiple prospective studies have shown that nonmagnified NBI examination is superior to WLI in detection of early esophageal lesions for screening of high-risk patients (10)(11)(12)(13) (15). In addition, NBI endoscopy also had a higher specificity comparing to Lugol chromoendoscopy (per lesion analysis 82% vs. 37%).…”
Section: Review Articlementioning
confidence: 99%
“…There are studies showing that associating lugol iodine test with other optical enhancement examination methods like NBI, SPIES, methylene blue or toluidine blue staining test provide better results concerning macroscopic examination of the head and neck tumor [20,21].…”
Section: Resultsmentioning
confidence: 99%